Reader's Digest, How Is It Done? - Reader's Digest (The Reader's Digest Association Limited UK, 1990)
An informative look at the ingenuity of man. Find out how holograms gives a three-dimensional picture, how nature photographers take their seemingly impossible pictures or what advances have been made in cloning. Discover how genetic finger-printing works or how astronauts dispose of bodily wastes.